2015
DOI: 10.1038/npp.2015.97
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Opioid Signaling in the Medial Prefrontal Cortex is Required for the Expression of Hunger-Induced Impulsive Action

Abstract: Opioid transmission and dysregulated prefrontal cortex (PFC) activity have both been implicated in the inhibitory-control deficits associated with addiction and binge-type eating disorders. What remains unknown, however, is whether endogenous opioid transmission within the PFC modulates inhibitory control. Here, we compared intra-PFC opioid manipulations with a monoamine manipulation (d-amphetamine), in two sucrose-reinforced tasks: progressive ratio (PR), which assays the motivational value of an incentive, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 50 publications
0
45
1
Order By: Relevance
“…Hsu, Kanoski, and colleagues have recently shown that vHP GLP-1R activation potently reduced food intake in rats, with ~40% reduction in 24hr chow intake and ~50% reduction in 24hr Western diet intake (68). These intake reducing effects are physiologically relevant to normal feeding, as vHP administration of the selective GLP-1R antagonist, exendin-(939), increased food intake.…”
Section: Endocrine Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hsu, Kanoski, and colleagues have recently shown that vHP GLP-1R activation potently reduced food intake in rats, with ~40% reduction in 24hr chow intake and ~50% reduction in 24hr Western diet intake (68). These intake reducing effects are physiologically relevant to normal feeding, as vHP administration of the selective GLP-1R antagonist, exendin-(939), increased food intake.…”
Section: Endocrine Communicationmentioning
confidence: 99%
“…Extensive direct projections are also observed from the vCA1 and vSub neurons to the mPFC (infralimbic and prelimbic subregions) (53, 85), which has recently been linked to reward-driven feeding via D1R (8) and opioid receptor signaling (9). Nucleus accumbens core and shell neurons, other key targets of VTA dopamine signaling, receive substantial innervation from the vSub (8688).…”
Section: Neuroanatomical Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to driving feeding itself, μ-OR stimulation in vmPFC also robustly amplifies responding in a sucrose-reinforced progressive ratio (PR) task and promotes ‘impulsiveness-like’ deficits in differential reinforcement of low response rates task (DRL) (Selleck et al 2015). Together, these effects indicate that cortical μ-OR stimulation increases the motivational value of food and energizes food-seeking repertoires, as well as disrupting inhibitory control over food-seeking.…”
Section: Feeding-modulatory Opioid Actions In the Pfcmentioning
confidence: 99%
“…Conversely, activation of the Acb via AMPA receptor stimulation (possibly arising from glutamatergic PFC projections) inhibits feeding, partly through descending inhibitory control over the hypothalamus, but also through the recruitment of non-food-directed behaviors. The incoherent engagement of these parallel ‘feeding-driver’ and ‘feeding-limiter’ pathways by opioid signaling could result in disorganized, impulsive food-seeking behaviors, such as those engendered by μ-OR stimulation in ventromedial PFC (Mena et al 2011; Selleck et al 2015). Fig.…”
Section: Motivational Effects Of Telencephalic Opioids: a Cortico-strmentioning
confidence: 99%